(untitled) (Medico Legal Update, 2021)
Objective: To assess the viability of TENS in diminishing agony and increasing function following TKR. Sample: 30 subjects (age>55years)chose based on consideration and avoidance standardsare included in the study. Method: 30 subjects were taken in the study,chosen based on consideration and rejection models and arbitrarily assigned to each group. Group 1 and group2. Experimental group (group 1) received TENS and exercise while control group received only exercises for 20 days (6 days per week). Functional testing was done using a questionnaire. Results: Paired t-test was used for statistical analysis. There was huge distinction between the two groups (A & B). The experimental group has significant improvement then the observational group. The pain VAS score has more difference. There was no significant difference in ADL activities score. Conclusion: It was concluded that applying TENS along with exercises on initial days of rehabilitation shows better results and increases the recovery process.